Prevalence of gastroesophageal reflux disease and its associated risk factors among the adult population of Mthatha, Eastern Cape, South Africa - Nomonde Ndyalvan; Mirabel K. Nanjoh; Monwabisi Faleni; Wezile W. Chitha; Sibusiso C. Nomatshila (PLoS ONE, 2025)
Epidemiological data on gastroesophageal reflux disease (GERD) reveal variations in prevalence rates and risk factors, which are still to be elucidated in the South African setting. Population-specific data are needed to contribute to the understanding of the pathophysiology of GERD. This study aims to determine GERD’s prevalence and associated risk factors among Mthatha residents. A descriptive cross-sectional study was carried out with a systematically sampled 353 adults attending the outpatient department of a secondary health care facility using the standardized GERD questionnaire (GerdQ) for screening and diagnosis. Descriptive and inferential statistics were performed with the aid of SPSS version 26. The prevalence of GERD was 32.0 percent (CI: 27.3% to 37.0%). Only 6.5 percent had an 89% likelihood of having GERD. Over half (53.1%) had GERD with little effect on day-to-day activities. The most common symptoms were heartburn at 49.6 percent, sleep disturbance at 34.8 percent, chest pain at 32.3 percent, and regurgitation at 32.3 percent, and were mild in most of them. Hypertension (OR = 3.0, CI: 1.5–6.4, p = 0.003) and eating more than three meals a day (OR = 4.2, CI: 1.9–9.2, p < 0.0001) were the major risk factors for GERD. The GERD rate of one in every three people is higher than the global rate of one in every six. The association of GERD with hypertension requires consideration of screening for GERD in patients with hypertension. Community education on proper dietary habits and the consequences of excess daily meals is needed to interrupt the development of GERD in the current population.